The Impact of Human Resource Management Practices on the Role of Individuals in Implementing the Global Institutional Excellence Model E.F.Q.M. at organizations. Descriptive and analytical study - Al-Rakhis, Fatima Mohammed Ibrahim (Journal of Economic, Administrative and Legal Sciences, 2019)
This study aimed to identify the impact of human resource management practices on the role of individuals in applying the global institutional excellence model، depending on descriptive theoretical analytical approach. The results showed a relationship between human resource management practices and the role of individuals in applying the global institutional excellence model. In addition to the impact of traditional and modern practices of human resources management in activating the role of individuals towards the application of this model. One of the most important recommendations of the study is to develop human resources management activities and organizational competencies in a manner appropriate to the nature of institutional excellence and linking the functions and roles of individuals and the standards of institutional excellence.